Optimum temperature for the growth form of tiger grouper (Epinephelus fuscoguttatus ♀) × giant grouper (E. lanceolatus ♂) Hybrid - Moumita De; Mazlan Abd. Ghaffar.; Yosni Bakar; Zaidi C. Cob; Simon Kumar Das (Penerbit Universiti Kebangsaan Malaysia, 2016)
The growth form and condition of the tiger grouper × giant grouper (TGGG) hybrid were evaluated under four temperatures (22°C, 26°C, 30°C, and 34°C) and two diets (pellet and shrimp). The growth form of fish was determined over a 30 day experimental period using the length–weight relationship (LWR) method. The TGGG hybrid grouper exhibited a negative allometric growth (b < 3) at all temperatures and diets at the beginning of the experiment (0 day), which indicated that fish would become lighter as they increased in size. Conversely, toward the end of the experiment (30 d), the TGGG hybrid grouper showed a negative allometric growth (b < 3) at 22°C and 34°C on both pellet and shrimp diet as well as demonstrated an isometric growth (b = 3) at 26°C fed on both diet and 30°C on pellet diet only, which indicated that the shape of the fish would not change with increasing weight and length. However, a positive allometric growth (b > 3) was observed at 30°C when the fish were fed on shrimp diet, which indicated that fish weight would increase with increasing length and size. The condition factors (K and Kn) in the initial (0 d) and final (30 d) measurements were greater than 1, thereby indicating the wellbeing of the TGGG hybrid grouper, except for those fish fed on both pellet and shrimp diet under 22°C and 34°C. Therefore, diet did not have a significant effect (p > 0.05) on the growth and condition of TGGG hybrid grouper, whereas temperature significantly influenced the growth and condition of the fish. All in all, grouper farmers can culture TGGG hybrid grouper between 26°C and 30°C, whereas the best growth and condition could be observed by culturing the fish at 30°C fed on shrimp.